Minimalism and its Psychological and Social Reflections on the User of Interior Space (Journal of the College of Basic Education, 2025)
Minimalism, or the art of extreme simplicity, is not merely a trend in interior design but a life philosophy that seeks to liberate the individual from the burden of material ownership. In a world where daily life is crowded with details and possessions, minimalism calls for reducing these details to their essence, opening space for mental tranquility and the expansion of the spirit. On a psychological level, this approach enhances a person's sense of comfort and inner balance, as the space becomes a reflection of mental clarity and self-harmony. Socially, minimalism contributes to a shift in values, where the importance of consumption fades in favor of seeking deeper experiences and meanings. It is a quiet rebellion against the culture of material excess, encouraging individuals to reflect on their relationship with themselves and the world around them, leading to a life of greater depth, free from both external and internal noise.